2017
DOI: 10.1086/688445
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Effects of High Yolk Androgen Levels on Constitutive and Cell-Mediated Immune Responses in Nestlings of an Altricial Passerine

Abstract: Avian embryos are exposed to yolk androgens that are incorporated into the egg by the ovulating female. These steroids can affect several aspects of embryo development, often resulting in increases in overall size or the speed of growth of different traits. However, several studies suggest that they also entail immune costs to the offspring. In this study, we explored whether variation in yolk androgen concentration affected several measures of the constitutive and cell-mediated immune axes in the spotless sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…Of two previous studies manipulating breeding stress in the closely related European starling ( Sturnus vulgaris ), one found that negative effects were restricted to female offspring (Rowland, Love, Verspoor, Sheldon, & Williams, ), whereas the other study found negative effects in males (Nettle et al., ). Although this discrepancy does not allow us to derive a general conclusion, it does underline the fact that the two sexes tend not to respond equally to developmental stressors (Muriel et al., ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Of two previous studies manipulating breeding stress in the closely related European starling ( Sturnus vulgaris ), one found that negative effects were restricted to female offspring (Rowland, Love, Verspoor, Sheldon, & Williams, ), whereas the other study found negative effects in males (Nettle et al., ). Although this discrepancy does not allow us to derive a general conclusion, it does underline the fact that the two sexes tend not to respond equally to developmental stressors (Muriel et al., ).…”
Section: Discussionmentioning
confidence: 95%
“…The fact that only females responded with higher corticosterone levels could be explained by their smaller size, which probably results in a lower competitive ability to access food from parents (Oddie, ). It is often found that sexes differ in environmental sensitivity to stressors (Muriel, Perez‐Rodriguez, Ortiz‐Santaliestra, Puerta, & Gil, ), but a large meta‐analysis has shown that there are no general patterns across animals in relation to sex or size (Jones et al., ). Most likely, the phenomenon is specific to different taxonomic groups and is possibly explained by differences in their developmental mode.…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant, antiviral, and anti-inflammatory activities were contributed by several metabolites (13,16-docosadienoic acid, erucic acid, eicosadienoic acid, and 5Z,8Z,11Z,14Z,17Z-eicosapentaenoic acid) engaged in the biosynthesis of the unsaturated fatty acid pathway (Weldon et al, 2007;Chen et al, 2020;Liang et al, 2020). Immunosuppressive effects were manifested by the metabolites (androstenedione, 5-androstene-3, 17-dione, testosterone, 5-α-androstane-3, 17-dione, dehydroepiandrosterone, and 3,4-dihydroxy-9,10-secoandrosta-1,3,5(10)-triene-9,17-dione) pertaining to steroid degradation (Muriel et al, 2017). The adhesion of flagellum, biofilm formation, virulence factor gene transcription, and production of toxins of bacteria are affected by bacterial pheromones (N-hexanoyl-l-homoserine lactone, N-heptanoylhomoserine lactone, and N-octanoyl-l-homoserine lactone) involved in the quorum-sensing pathway, thereby directly promoting the infection by pathogens (Yang et al, 2013;Li et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…on the immune system (e.g. the cell-mediated immune response, Muriel et al 2017) or on the resistance to oxidative stress (Alonso-Alvarez et al 2017). Following the logic of previous research on androgen associated trade-offs (Folstad and Karter 1992), it has been suggested that there may be similar tradeoffs between costs and benefits of maternal androgens (Groothuis et al 2005;Muriel et 7 al.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, no study to date has covered the entire lifespan of individuals. Still, these kind of studies are decisive to evaluate the overall effects of maternal hormones on fitness and their adaptive role, especially in the perspective of their sex-specific activity (Muriel et al 2017). Although the strength and direction of effects vary depending on the species, many of the studies involving egg-androgen manipulation suggest that female nestlings do not benefit from elevated androgen levels, whereas males do (Saino et al 2006;von Engelhardt et al 2006;Ruuskanen and Laaksonen 2010;Muriel et al 2015bMuriel et al , 2017.…”
Section: Introductionmentioning
confidence: 99%